Steady the buffs! a regiment, a region, and the Great War - Connelly, Mark (Oxford University Press, 2006)
This is an examination of the backgrounds and attitudes of officers, men, and their families to the war and looks at its impact on the military and civil community. The book tests the theories about the British army in the war and some of the conclusions of modern military historians.